2019
DOI: 10.1002/anie.201906049
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Armed, Hydrophilic Transition Metal Complex as a Paramagnetic NMR Probe

Abstract: Synthetic metal complexes can be used as paramagnetic probes for the study of proteins and protein complexes. Herein, two transition metal NMR probes (TraNPs) are reported. TraNPs are attached through two arms to a protein to generate a pseudocontact shift (PCS) using cobalt(II), or paramagnetic relaxation enhancement (PRE) with manganese(II). The PCS analysis of TraNPs attached to three different proteins shows that the size of the anisotropic component of the magnetic susceptibility depends on the probe surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 81 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…The tags delivered significantly different tensor orientations as evidenced by the PCS isosurfaces shown in Figure 10. 280 Recently, the double-anchored probe CLaNP-13 (Figure 9, 85) was designed for DEER studies in living cells. 281 By virtue of two maleimide groups, CLaNP-13 forms thioether bonds with cysteine residues, which in a cellular environment are more stable than disulfide bonds.…”
Section: Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The tags delivered significantly different tensor orientations as evidenced by the PCS isosurfaces shown in Figure 10. 280 Recently, the double-anchored probe CLaNP-13 (Figure 9, 85) was designed for DEER studies in living cells. 281 By virtue of two maleimide groups, CLaNP-13 forms thioether bonds with cysteine residues, which in a cellular environment are more stable than disulfide bonds.…”
Section: Chemicalmentioning
confidence: 99%
“…Subsequent study of this tag and metal complexation mode in the same protein and in T4Lys K147C/T151C revealed additional species also with Co(II) ions and difficulties to achieve complete saturation of the metal Chemical Reviews pubs.acs.org/CR Review binding site. 280 A systematic exploration of the best binding partner for an IDA-SH or NTA-SH tag attached to a cysteine residue in position i of an α helix indicated that the IDA-SH tag forms the best Ln(III) binding sites together with an aspartate residue in position i + 4, while the sterically more demanding NTA-SH tag produces the best sites in combination with a glutamate residue in position i − 4. 330 As secondary structure predictions identify amphipathic α helices with good reliability, this approach is of interest for proteins of unknown 3D structure.…”
Section: Chemicalmentioning
confidence: 99%
“…This leads to multiple NMR signals at some pH values. Two-armed tags that bind transition metals are also available (Miao et al 2019). As transition metals have smaller anisotropy tensors, these are more applicable to systems where the tagging site is close to the binding site.…”
Section: Paramagnetic Tags For Protein Conjugationmentioning
confidence: 99%
“…Apart from non‐natural amino acids, paramagnetic tags generally target cysteines. The standard strategy is the conjugation by formation of a disulfide bond: this technique has been widely used but it is hampered by the stability of the bond formed . Thus, in recent years, much effort has been concentrated on the design of paramagnetic tags that are stable under reducing conditions once attached to the protein, and which could also be used in cells .…”
Section: Introductionmentioning
confidence: 99%